Role of neuroinflammation in the pathogenesis of glaucomatous optic neuropathy - E.A. Egorov; V.E. Korelina; D.V. Cherednichenko; I.R. Gazizova (РМЖ "Клиническая офтальмология")
E.A. Egorov1, V.E. Korelina2, D.V. Cherednichenko3, I.R. Gazizova3 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2LLC "American Medical Clinic", St. Petersburg, Russian Federation 3N.P. Bekhtereva Institute of the Human Brain, St. Petersburg, Russian Federation This article reviews recent studies on the etiology and pathogenesis of primary open-angle glaucoma (POAG). POAG is now considered a neurodegenerative disease associated with neuroinflammation. Neuroglia plays a key role in the development of neuroinflammation. In impaired homeostasis, microglia is activated to prevent retinal alterations triggered by glutamate excitotoxicity. Macrophages, being still active, release cytokines in the extracellular space and produce matrix metalloproteinases. The result is an increased degradation of collagen fibers of the lamina cribrosa and development of glaucomatous optic neuropathy. Macroglia (astrocytes and Muller cells) are also involved in retinal immunoregulation. Astrocytes produce neurotrophic brain factor which promote the survival of damaged neurons. Additionally, these cells secrete fibrillar proteins that regenerate the extracellular matrix but form a glial scar, thereby inhibiting axonal transport and limiting t he regeneration of damaged axons. The activation of microglia and macroglia in glaucoma precedes the loss of retinal ganglion cells. Determining the activity of retinal ganglion cells helps identify specific biomarkers of early glaucoma. Early diagnosis of POAG prevents irreversible damage. The authors discuss potential ways to regulate the activity of glia by stimulating the release of neurotrophic factors and suppressing glia hyperactivity. Keywords: primary open-angle glaucoma, neurodegenerative disease, neuroinflammation, macroglia, microglia, neurotrophic factors. For citation: Egorov E.A., Korelina V.E., Cherednichenko D.V., Gazizova I.R. Role of neuroinflammation in the pathogenesis of glaucomatous optic neuropathy. Russian Journal of Clinical Ophthalmology. 2022;22(2):116–121 (in Russ.). DOI: 10.32364/2311-7729-2022-22-2-116-121.